2022
DOI: 10.1017/s0022215122001220
|View full text |Cite
|
Sign up to set email alerts
|

The Newport Quinsy Simulator

Abstract: Background The junior otolaryngologist is responsible for recognition and drainage of the peritonsillar abscess. Although other simulators have been proposed, there is still a need for an accessible, educationally useful, low-cost peritonsillar abscess simulator to build skills and confidence in the novice. Methods The peritonsillar abscess simulator was constructed from basic disposable healthcare equipment and a party balloon. Evaluation of this Newport Quinsy Simulator was performed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…1). Ten articles were included in the final review, five from the US, 11,12,[19][20][21] three from the UK, [22][23][24] and two from Canada. 25,26 Two studies trained participants on both needle aspiration and I&D, 11,19 four studies on I&D only, 12,21,25,26 and four on needle aspiration only.…”
Section: Demographics and Tasks (Fig 1 And Table Ii)mentioning
confidence: 99%
See 3 more Smart Citations
“…1). Ten articles were included in the final review, five from the US, 11,12,[19][20][21] three from the UK, [22][23][24] and two from Canada. 25,26 Two studies trained participants on both needle aspiration and I&D, 11,19 four studies on I&D only, 12,21,25,26 and four on needle aspiration only.…”
Section: Demographics and Tasks (Fig 1 And Table Ii)mentioning
confidence: 99%
“…25,26 Two studies trained participants on both needle aspiration and I&D, 11,19 four studies on I&D only, 12,21,25,26 and four on needle aspiration only. 20,[22][23][24] Of the four needle aspiration studies, one utilized ultrasound guidance during the procedure (Table II). 20 The proportion of junior residents with minimal previous exposure to PTA (≤5 procedures) was indicated in 3 studies and was found to range from 87.5% to 100%.…”
Section: Demographics and Tasks (Fig 1 And Table Ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…Simulation-based learning in ENT is already established 4,5,6 ; however, most of these courses are only delivered to senior trainees, 7,8,9 with only a few documented to be aimed at junior doctors 10 or medical students. 11 Moreover, with the ENT simulation models described in the literature, there is little validation or demonstrated educational impact assessed.…”
Section: Introductionmentioning
confidence: 99%